(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Osteoarthritis is most common type of degenerative disease affecting thousands of Indian citizens. Objective-1. To assess the quality of life before exercise therapy among patients with osteoarthritis in experimental and control group.2. To assess the quality of life after 15 days after exercise therapy among patients with osteoarthritis in experimental and control group. 3.To compare the quality of life between the experimental and control group before and after 15 days of exercise therapy.4. To correlate the level of participation with quality of life among patients with osteoarthritis in experimental group.5. To associate the quality of life among osteoarthritis patients with their selected demographic variables in experimental and control group. Methodology- evaluative approach. True Experimental with Pre-test and Post-test Control Group design was used. 60 sample were selected with the help of simple random sampling technique The data was collected for a period of fifteen days i.e. 1-08-12 to 15-08-12. S.N.R District Hospital, Kolar. Result- In Pre test total number of patients (100%) had low quality of life in the Experimental Group. In the Control group, majority 29 (97.3%) of patients had low quality of life, 1 (3.3%) of patients had moderate quality of life and no patients had high quality of life. After exercise therapy in the Experimental group majority 28 (93.4%) patients had moderate quality of life, 2 (6.6%) patients had high quality of life and no patients had low quality of life and the Control Group remained the same. Conclusion- exercise theraphy improve quality of life among patients with osteoarthritis